Epithelial-to-mesenchymal transition markers are differentially expressed in epithelial cancer cell lines after everolimus treatment - Goncalves, Bryan Ortero Perez; De Andrade, Warne Pedro [UNESP]; Da Conceicao Braga, Leticia; Fialho, Silvia Ligorio; Silva, Luciana Maria (Spandidos Publ Ltd, 2020)
The epithelial-to-mesenchymal transition (EMT) is a phenomenon during which cancer epithelial cells undergo changes in plasticity and lose cell-cell adhesion with consequent remodeling of the extracellular matrix and development of mesenchymal characteristics. Long non-coding RNAs (lncRNAs) have been described as EMT modulation markers, becoming a promising target in the development of new therapies for cancer. The present study aimed to investigate the role of everolimus at 100 nM as inductor of the EMT phenomenon in cell lines derived from human breast (BT-549), colorectal (RKO-AS45-1) and ovary (TOV-21G) cancer. The integrity of cellular junctions was monitored using an in vitro model of epithelial resistance. The results demonstrated that the EMT genes ZEB1, TWIST1 and TGFB1 were differentially expressed in cells treated with everolimus compared with in untreated cells. lncRNA HOTAIR was upregulated post-treatment only in BT-549 cells compared with in untreated cells. After treatment with everolimus, the intensity of fluorescence of P-cadherin decreased, and that of fibronectin increased in RKO-AS45-1 and TOV-21G cells compared with control cells. The transepithelial electrical resistance at the RKO-AS45-1 monolayer treated with everolimus started to decrease at 48 h. The changes in the gene expression and epithelial resistance may confirm the role of everolimus in EMT.
Keywords: EMT; cancer; everolimus; HOTAIR; biomarker